Pemanfaatan Data Citra Satelit Multi Sumber dalam Analisis Spasial Jumlah Kasus Demam Berdarah Dengue (DBD) di Pulau Jawa Tahun 2022 - Magfirah, Deanty Fatihatul; Pramana, Setia (Seminar Nasional Official Statistics, 2024)
Dengue Hemorrhagic Fever (DHF) is one of the world's dangerous infectious diseases, especially in tropical areas, such as Indonesia. The spread of dengue virus is generally caused by an environment that supports the development of DHF vectors, including temperature, rainfall, humidity, surface water, population density, and urbanization. The purpose of this study was to obtain environmental factors that significantly influence the number of DHF cases in Java and to group districts/cities according to the same characteristics by utilizing Sentinel-2, Sentinel-5P, Landsat-8 and CHIRPS satellite imagery. Descriptive analysis and inferential analysis were carried out with Mixed Geographically Weighted Regression (MGWR) spatial modeling for spatial regression analysis of the characteristics of each region. Environmental factors obtained from the analysis results describe each characteristic of the district/city area according to their respective local conditions and six groups are formed with the same regional characteristics and are located close to each other.